Soil chemical properties in a Typic Quartzipisamment under different management systems in Brazilian savanna in Mato Grosso State, Brazil - Frazão, Leidivan Almeida; Píccolo, Marisa de Cássia; Feigl, Brigitte Josefine; Cerri, Carlos Clemente; Cerri, Carlos Eduardo Pellegrino (Pesquisa Agropecuaria Brasileira, 2008)
The objective of this work was to evaluate the effect of different land uses and soil management systems, on chemical characteristics of a Typic Quartzipisamment in the savanna (Cerrado) of Mato Grosso State, Brazil. The treatments studied were: native cerrado; pasture with low productivity for 22 years; conventional tillage with one and four years and different crop successions; and no-tillage for five years. Soil carbon and nitrogen, pH, potential acidity, cation exchange capacity (CEC), available phosphorus, exchangeable bases and base saturation were determined. The cerrado and pasture treatments had the lowest pH, available phosphorus, calcium and magnesium values; and the low soil carbon level under pasture system led to lower soil potential CEC. Liming in conventional tillage and no-tillage promotes an increase in soil calcium and magnesium content. In these systems, the soil base saturation (V%) is higher in the areas with a greater time of implantation (4 and 5 years). Although Neossolo Quartzipisamment has limitations for cultivation purposes, due to low inherent fertility, this soil type may have agricultural potential if managed properly.
Keywords: soil fertility; pastures; conventional tillage; no-tillage